Role of imf lending preconditions in nigeria - Mohd Afandi, Salleh (2021)
Nigerian government was seeking help from the IMF , because of which the economy has deteriorated considerably as the Institution recommended some structural conditions before the country is supported which was proclaimed as a panacea for solving the development problem within the country. Therefore, the aim of this study was to seek whether the policies contribute to solving the development problems Nigeria is facing. The study utilized Neoliberalism as conceptual framework, using a qualitative research approach, the data were obtained using an in -depth interviews. With the assistance of Qualitative Data Analysis software, NVivo 12 for Microsoft Windows, the collected data was analyzed using content and thematic analysis. The results indicate that the policies prescribed by the IMF are in place to promote Nigeria 's socio-economic prosperity. Some of the policies prescribed by the IMF include deregulation, privatization, removal of subsidies, currency devaluation and trade liberalization. The study also revealed that over the years, IMF policies have contributed and impeded Nigerian economic growth tremendously. The study advises that the government should formulate plans and initiatives to cushion the detrimental effects of any policies that can be directly or indirectly enforced. This will guarantee that the country is not politically or financially fully destabilized.